La reparación del incumplimiento del plazo razonable en el Tribunal de Justicia de la Unión Europea y una posible consecuencia para el estatus de los derechos fundamentales - Edorta Cobreros Mendazona (Revista Vasca de Administración Pública)
Reasonable period of time is currently a fundamental right in the EU legal order. The compensation of damages that might have been caused by its infringement is a discussed matter and there the interpretation provided by the Court of Justice has experienced a clear evolution. The last position on this matter calls for filing an action for damages before the General Court in order to obtain a compensation. This raises a possible new consequence within the legal regime of the non contractual liability of the European Union, that is that the impairment of a fundamental right might be considered per se as a sufficiently serious breach which would strengthen the prevalent position of fundamental rights in the legal order of the European Union.